2005
DOI: 10.1093/alcalc/agh221
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Early Alcohol Withdrawal in Chronic Alcoholics

Abstract: Complete alcohol abstinence must be recommended to all hypertensive alcoholics, as AW-induced transient hypertension was found to be harmless in all our subjects, and abstinence leads to a complete recovery from hypertension in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…Our findings demonstrating that ethanol withdrawal causes a significant increase in blood pressure are in accordance with previous observations in humans (Ceccanti et al, 2006;Clark & Friedman, 1985;King, Bernardy, Parsons, & Lovallo, 1996). Some studies suggested that the elevation in blood pressure observed during ethanol withdrawal is transitory (Ceccanti et al, 2006;Clark & Friedman, 1985).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings demonstrating that ethanol withdrawal causes a significant increase in blood pressure are in accordance with previous observations in humans (Ceccanti et al, 2006;Clark & Friedman, 1985;King, Bernardy, Parsons, & Lovallo, 1996). Some studies suggested that the elevation in blood pressure observed during ethanol withdrawal is transitory (Ceccanti et al, 2006;Clark & Friedman, 1985).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies suggested that the elevation in blood pressure observed during ethanol withdrawal is transitory (Ceccanti et al, 2006;Clark & Friedman, 1985). However, there is evidence that ethanol withdrawal induces a persistent alteration of blood pressure regulation even when resting pressures are normal, further suggesting that ethanol withdrawal may predict future cardiovascular abnormalities (King et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that folic acid supplementation is beneficial in preventing the increase in the arterial blood pressure associated with long-term chronic alcohol intake. Along these lines, Ceccanti et al (2005) obtained similar results, finding that hypertension was moderated in chronic alcohol patients. Furthermore, after 18 days of abstinence, arterial blood pressure values were reduced, something that could also be in agreement with our hypothesis which implies the accumulation of aldosterone as one of the main causes of the increase in arterial blood pressure to be found among chronic alcoholics since during this period serum levels of aldosterone (as well as other substances that cause hypertension) might diminish.…”
Section: Cardiac Frequency and Arterial Pressure Studiessupporting
confidence: 59%
“…The nature of the effect of cessation on the physiology of the individual is dependent upon the substance. For example, cessation of alcohol [21], cannabis [22], and opiate [23], use leads to an increase in such physiological measures in those who abuse these substances. Whereas, cessation of usage of MDMA [24,25], nicotine [26], and stimulants [25], depresses these physiological systems in individuals addicted to them.…”
Section: Introductionmentioning
confidence: 99%